A Dictionary for the Modern Pianist - Siek, Stephen (Rowman & Littlefield Publishers, 2016)
A Dictionary for the Modern Pianist combines nearly four hundred entries covering classical and popular pianists, noted teachers, terminology germane to the piano’s construction, and major manufacturers—both familiar firms and outstanding, independent builders who have risen to the forefront in recent years. Speaking to the needs of the modern performer, it also includes entries on jazz and pop artists, digital pianos, and period instruments. As a resource for professionals and students, A Dictionary for the Modern Pianist is also accessible to more general readers, as all of its topics are presented in clear, readable expositions. Drawing on the most recent research of numerous specialists, author Stephen Siek emphasizes the piano's uniquely rich heritage, giving pianists a renewed appreciation for the famous artists and teachers who have shaped their art. Transcending simple alphabetical definitions, the dictionary’s careful attention both to legacy and detail make it an invaluable addition to any pianist’s library. Titles in the Dictionaries for the Modern Musician series offer novice and advanced musicians key information on the field of study and performance of a major instrument or instrument class. Unlike other encyclopedic works, contributions to this series focus primarily on the knowledge required by the contemporary musical student or performer. From quick definitions of confusing terms to in-depth overviews of history and tradition, the dictionaries are ideal references for students, professionals, and music lovers of all kinds.